MSW Students' Use of SBIRT: Toward an Understanding of the Gap Between Classroom and Field Education. Issue 1 (3rd April 2019) - Collin, Cali-Ryan; Putney, Jennifer M.; Halmo, Rebekah; Ogden, Lydia; Mcmanama O'brien, Kimberly H.
Abstract : Increased visibility of substance use as a public health concern has prompted Screening, Brief Intervention, and Referral to Treatment (SBIRT) training initiatives; however, barriers to SBIRT use in social work practice remain. We aimed to identify factors differentiating MSW students who used SBIRT in practice from those who did not. Independent-samples t tests compared attitudes and beliefs of students who did and did not use SBIRT. Significant differences were detected between groups in SBIRT-related expectation of use, benefit to patients or clients, and importance of learning to screen and intervene in substance use. SBIRT training should emphasize relevance and benefit to diverse patients and clients in various settings.